Drivers of airport scheduled traffic in European winter tourism areas: infrastructure, accessibility, competition and catchment area - Suau-Sanchez, Pere; Voltes-Dorta, Augusto (Elsevier, 2019)
Ski resorts in Europe are major tourism destinations that can generate traffic for their local airports. These small mountain airports can offer the airlines unparalleled accessibility to the resorts, but their catchment areas are typically not well populated. Local authorities are keen to develop scheduled flights but have failed many times in the past. In this context, there is no previous study that analyses the drivers of scheduled airport traffic in winter tourism regions. To that end, we compiled a large dataset of European airports and ski resorts and carry out a Poisson regression. Results show that catchment area, competition, and infrastructure outweigh accessibility to ski resorts as the main drivers of scheduled traffic at small mountain airports. This is linked to the dominance of low-cost carriers that prefer to operate out of major airports with larger aircraft. Small airports are recommended to focus on premium markets with smaller aircraft.
Keywords: Winter tourism; Airport development; Ski resorts; Poisson regression